Can we improve delivery room monitoring for newborns? A novel photoplethysmographic heart rate monitor evaluated among stable nicu infants. (7th June 2011) - Mann, C; Ward, C; Grubb, M; Teoh, J; Crowe, J; Hayes-Gill, B; Marlow, N; Sharkey, D
Abstract : Background: Heart rate (HR) is considered the most reliable indicator of successful newborn resuscitation. Current recommended assessment is by auscultation but this is subject to human error1 and can interrupt resuscitation. Pulse oximetry is sometimes used but is subject to long acquisition times and poor signal with reduced perfusion.2 An improved method of monitoring HR during these crucial minutes may optimise outcomes for infants requiring resuscitation. Aims: To validate a novel, reflectance photoplethysmographic sensor to measure HR. Advantages of this device include (1) forehead placement reduces the risk of hypothermia in preterm infants, (2) Rapid placement and acquisition time, 3 (3) reliable in poor perfusion states, (4) continuous and hands free. Methods: We evaluated the sensor in 50 infants (26–42 weeks gestation) admitted to our Neonatal Intensive Care Unit. The sensor was on the forehead and 20-min recordings made with simultaneous routine ECG monitoring to provide the comparator. Reliability was calculated as the percentage positive agreement within 5 bpm of the ECG HR. Results: Data were excluded for six infants due to poor or incomplete ECG traces. Overall median agreement with ECG was 88% (IQR 79%, 95%). Conclusion: Our novel sensor detects a pulsatile signal in stable newborn infants with reliability ≥88% for a clinically useful agreement of +/−5 bpm. We identified motion artefact as a significant contributor to reduced reliability and are optimising sensor fixation to reduce this. Ongoing trials to validate this device among term and preterm infants in the delivery room are underway.